Analisis Penerapan Tax Review Sebagai Dasar Evaluasi Kewajiban Perpajakan Pada PT. XYZ - Masih, Ni Nyoman; Sudiana, I Wayan; Yuliantari, Ni Putu Yeni (Hita Akuntansi dan Keuangan, 2025)
Taxes are the main source of state income which is used to finance the budget related to development and state interests. A mandatory person is an individual or entity who has the authority to pay taxes, withhold taxes and collect taxes, and has rights and obligations related to taxation in accordance with applicable regulations. Even though the largest contribution to taxes comes from Corporate Taxpayers, the number of people paying taxes from this group is still relatively small. A tax review is a comprehensive review of a company's tax obligations and the implementation of fulfilling its obligations, from calculation to reporting, with the aim of assessing the level of tax compliance. This research aims to implement the implementation of Tax Review as a basis for evaluating tax obligations at PT. XYZ. Using qualitative research methods, this research collects research data in several ways, including interviews, observation and documentation. The results of this research show that a tax review is very useful in overcoming delays in tax payments so that XYZ company will start to be firm in billing customers so that the company's cash flow can be managed appropriately. PT XYZ has also been able to fulfill its tax obligations in accordance with applicable regulations, however, in implementing its obligations in the field, there are still several deficiencies that unintentionally occur, such as late payment of tax because there are still customers who have not made full transaction payments. Keywords: Tax Review, Tax Obligations, Tax